Microwave bottom-up route for size-tunable and switchable photoluminescent graphene quantum dots using acetylacetone: New platform for enzyme-free detection of hydrogen peroxide. (January 2015) - Umrao, Sima; Jang, Min-Ho; Oh, Jung-Hwan; Kim, Guntae; Sahoo, Sumanta; Cho, Yong-Hoon; Srivastva, Anchal; Oh, Il-Kwon
Abstract: We report a microwave sequential bottom-up route to produce green and blue luminescent graphene quantum dots (g-GQDs and b-GQDs) with size-tunable and switchable functionalities by tailoring the diameter size and functional groups via microwave carbonization and aromatization processes from acetylacetone as a starting organic solvent. The b-GQDs as the final product show only one emission peak at 433 nm and pH-independent blue luminescence, because two-step microwave irradiation could reduce the size and the oxygen-functional groups of the g-GQDs as an intermediate product. Also, the b-GQDs provide an exemplar enzyme-free platform for hydrogen peroxide detection through the electrochemical sensing due to much higher electron density and electron donating properties. In contrast, the g-GQDs show two different switchable photoluminescent emissions at ∼460 nm (P1) and ∼500 nm (P2): the P1 emission with sky-blue fluorescence originates from randomly conjugated oxygen-functional groups on the basal plane and/or edge of the g-GQDs and the P2 emission with green fluorescence results from quasi-molecular fluorophores formed by the electronic coupling of carboxylic acid groups.